A Statistical Study of the Moon's Magnetotail Plasma Environment. Issue 4 (7th April 2022) - Liuzzo, Lucas; Poppe, Andrew R.; Halekas, Jasper S.
Abstract: This study investigates the lunar plasma environment when embedded within Earth's magnetotail. We use data from 10 years of tail crossings by the Acceleration, Reconnection, Turbulence, and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) spacecraft in orbit around the Moon. We separate the plasma environments by magnetosheath‐like, magnetotail lobe‐like, and plasma sheet‐like conditions. Our findings highlight that the lobe‐like plasma is associated with low densities and a strong magnetic field, while the plasma sheet is characterized by higher densities and a weaker magnetic field. These regions are flanked by the fast, predominantly tailward flows of the terrestrial magnetosheath. During a single lunar crossing, however, the magnetotail displays a wide range of variability, with transient features—including reconnection events—intermixed between periods of lobe‐like or sheet‐like conditions. We compare and contrast the Moon's local magnetotail plasma to the environments near various outer‐planet moons. In doing so, we find that properties of the ambient lunar plasma are, at times, unique to the terrestrial magnetotail, while at others, may resemble those near the Jovian, Saturnian, and Neptunian moons. These findings highlight the complementary role of the ARTEMIS mission in providing a deeper understanding of the plasma interactions of the outer‐planet moons. Key Points: We use 10 years of data from the Time History of Events and Macroscale Interactions during Substorms‐Acceleration, Reconnection, Turbulence, and Electrodynamics of the Moon's Interaction with the Sun mission to constrain the lunar plasma environment within the terrestrial magnetotail We identify three predominant distributions of the magnetotail plasma, corresponding to the magnetosheath, lobes, and plasma sheet For these conditions, we calculate statistical properties of the local magnetic field, plasma bulk velocity, number density, and temperature